Applications of the KMV model to assess the default risk in the firm, a A case study of a sample of firms listed in the Abu Dhabi Securities Exchange for the period (2018-2019) - Benslim, Mohsen (Dirassat Journal Economic Issue, 2022)
This study aims to discuss the effectiveness of the KMV model in helping to assess and predict the default risk. To this end, the structural models and the conditions for their identification were shed light on, as well as the various theoretical frameworks of the KMV model and its methodology for measuring the default risk, as well as the steps for its application. Where it was applied to a sample of companies listed on the Abu Dhabi Securities Market. To achieve the goal of the study, the descriptive method was used to gain familiarity with the various aspects of the research. The study concluded that the KMV model is one of the most important models available to assess the default risk, and the ease of this model enables institutions and banks to standardize credit risks and help them to take the necessary and appropriate measures in the event of default.